High Performance Graphitic Carbon from Waste Polyethylene: Thermal Oxidation as a Stabilization Pathway Revisited - Choi, Dalsu; Jang, Dawon; Joh, Han-Ik; Reichmanis, Elsa; Lee, Sungho (AMER CHEMICAL SOC, 2017)
In this study, for the first time, thermal oxidation, which has only been considered as a degradation pathway for plastics, served as a simple and effective pretreatment protocol to modulate the chemical structure of linear low density polyethylene (LLDPE) for successful conversion of "noncarbonizable" LLDPE into an ordered carbon. More importantly, LLDPE based carbon could be graphitized into a highly ordered graphitic carbon with exceptional electrical performance exceeding that of Super-P, a pricey reference conductive agent for lithium ion battery fabrication. Upon thermal oxidative pretreatment, inherently noncarbonizable LLDPE was successfully transformed into an ordered carbon through heat treatment with a high conversion yield reaching 50%, a yield comparable to that obtained from polyacrylonitrile (PAN), a reference polymeric precursor. Systematic interrogation of the chemical structural evolution using X-ray diffraction, Raman, and dynamic scanning calorimetry (DSC) analysis, confirmed that an oxidation reaction occurred around 330 degrees C, which initiated transformation of aliphatic chains into cyclized ladder structures that allowed successful carbonization of LLDPE with high carbon yield. The thermally oxidized LLDPE evolved into a highly graphitic carbon that exhibited superior degree of ordering and electrical performance over a graphitized PAN counterpart. Finally, LLDPE waste, such as cling wrap and poly gloves was also successfully converted into an ordered carbon comparable to that obtained from the as-produced LLDPE precursor, suggesting opportunities associated with "upcylcing" of waste products. Thus, the proposed protocol represents an effective, potentially low-cost, and sustainable pathway providing for an exceptionally high quality conductive agent applicable in energy storage and flexible, printed electronics.
Keywords: LOW-DENSITY POLYETHYLENE; RAMAN-SPECTROSCOPY; AMORPHOUS-CARBON; POLYMERS; GRAPHENE; FILMS; REEXAMINATION; POLYPROPYLENE; COMPOSITES; CRYSTAL